Prevalence of and risk factors for nasal methicillin-resistant Staphylococcus aureus colonization among children in central Taiwan - Hui-Hsien Pan; Yhu-Chering Huang; Chih-Jung Chen; Fang-Liang Huang; Pei-Ju Ting; Jing-Yang Huang; Cheng-Hsun Chiu; Tzou-Yien Lin; Po-Yen Chen (Journal of Microbiology, Immunology and Infection, 2019)
Background/purpose: Staphylococcus aureus (S. aureus) causes diseases ranging from mild skin infections to invasive diseases. Carriage of S. aureus, including methicillin-resistant S. aureus (MRSA), is a significant risk factor for subsequent staphylococcal infection. Several studies discussed MRSA colonization in Taiwan, but mostly in northern Taiwan. This is the first study that estimates the prevalence of MRSA nasal colonization in healthy children and identifies the potential risk factors in central Taiwan. Methods: A total of 3144 healthy children aged 2–60 months who visited Taichung Veterans General Hospital (TCVGH) were screened for nasal S. aureus carriage from July 2005 to December 2010. Questionnaires included demographic information and potential risk factors for carriage of S. aureus were completed by parents/guardians. Results: Prevalence of MSSA and MRSA were 12.09% and 5.25%, respectively. The youngest group aged 2–6 months had the highest S. aureus carriage rate, and the carriage rate revealed a peak in summer. The nasal colonization of Streptococcus pneumoniae (S. pneumoniae) was a protective factor against S. aureus colonization. 85% of the MRSA colonizing isolates belonged to clonal complex 59/staphylococcal cassette chromosome type IV or VT, the local community clone in Taiwan. Conclusion: An increasing trend of MRSA nasal carriage rate in Taiwan had been brought forward, however, it was not observed in central Taiwan during the period of 2005–2010. We found a summer peak on both MRSA and MSSA carriages. Keywords: Central Taiwan, Children, Methicillin-resistant Staphylococcus aureus colonization